Viability of MCF7 Cells Exposed to Basolateral Secretion from CaCo2 Cells Pretreated with Fecal Waters from Breast Cancer Patients and Controls. (29th May 2020) - Bard, Jean-Marie; Bobin-Dubigeon, Christine; Luu, Huyen-Trang; Vacon, Françoise Le; Carton, Thomas; Nazih, Hassan
Abstract: Objectives: There is increasing evidence suggesting that microbiota may play a role in breast cancer disease and influence the disease severity. Several mechanisms may be involved in this relationship. Our hypothesis is that the role of microbiota in the disease may be at least partly related to its influence in gut lipid and lipoprotein metabolisms. This hypothesis was tested in an in vitro model combining MCF7 and Caco2 cells. Methods: 32 women newly diagnosed for breast cancer, before any treatment and 28 apparently healthy women provided their stools from which bacterial DNA was extracted and amplified by qPCR, targeting 16S rRNA sequences specific to bacterial groups. Fecal waters (FW) were also obtained from these stools. Intestinal Caco-2 cells grown on filter inserts were incubated apically with 10% FW for 24 h. Then, MCF-7 cells were incubated with the whole basolateral medium for 24 h. The viability of these cells was estimated by MTT test. In parallel, LXR, apolipoproteins AIV and E gene expression was estimated by RT QPCR in CaCo2 cells and short chain fatty acids (SCFA) were quantified in FW. A logistic regression model was used to establish the Odds ratios (OR) for the disease of MCF7 viability and CaCo2 gene expression. The relationship between % bacterial groups, CaCo2 gene expression, SCFA and viability was established by regression models. Results: Patients and controls differed by the MCF7 viability (1.05 [1.01–1.10], p = 0.04) and a tendency towards a difference was observed for apo AIV gene expression (0.63 [0.39–1.01], p = 0.055), (OR [5th-95th]). Viability was positively correlated with % Bifidobacterium sp.  (21.18 ± 7.66, p = 0.008) and negatively correlated with valerate (−2.849 ± 1.048, p = 0.009), (ß±s.d.). These correlations were maintained in a multiple regression model. Conclusions: Microbiota may interact with intestine cell lipid metabolism and therefore influence cancer disease through gut cell secretion or permeability. Funding Sources: Ligue Contre le cancer and private funds from Integrated Center for Oncology.